Famílias poliafetivas: Negação e reconhecimento - SAMPAIO, Ana Alice Torres (2023)
The aim of this work is to analyze the juridical and sociocultural impediments for the acknowledgement of polyaffective families in Brazil.With proposals to achieve the general goal, a qualitative approach methodology was used and it was developed a research with the combination of techniques, namely, exploratory, bibliographical, documentary and ethnographic, the last one was done through a field research with semi-structered interviews with members of polyaffective families.In this sense, after the introduction,, the first chapter of the theorectical reference aims to contextualize polyaffective families in the socialcultural and juridical order from the categories of kinship, gender, sex, family and affection, with a bibliographic review about the theories from Adriana Piscitelli (1998), Marylyn Strathern (2015), Lévi-Strauss (2012), Gayle Rubin (1949), Joan Scott (1989), Monique Witting (2022), Judith Butler (2003),beyond others theorists. On the second chapter of the theoretical reference, the goal is to show the grounds for the judgment of the Adjustment Request nº0001459-08.2016.2.00.0000, in this aspect this research also reveals itself documentary, cause it specifies the analysis of a judgment made by the National Council of Justice that prohibited the issuance by public charters of unions, from polyaffect in Brazil, based on the exposure of losing and writing votes, as well the counterpoint between them. Finally, the third chapter concerns on the section whose methodology was ethnography, in the digital mode, advocated by Cláudia Ferraz (2019), Daniel Miller (2021), Laura Gomes e Débora Leitão (2017), moreover, for being a field research it needed to be previosly submitted and approved by the Ethics and Research Committee of the University Hospital-HUUFMA. The first stage of ethnography consisted of observing and mapping the profiles of polyaffective families maintained on the social network Instagram, subsequently, on the second stage were done interactions with the interlocutors through direct messages,likes and comments on the posts [photos and vídeos] in order to invite them to participate in the survey by granting interviews on the Google Meet plataform, after acceptance and prior completion of the Free and Informed Consent Term by the referred families, Nine interviews[09] were made with [09] nine trisals from Brazil, among which [04] four are domiciled in the Southesat region of the country,[04] four in the Northeast region and [01] one in the South region ,thus [27] twenty seven interlocutors were heard. Finally, the transcriptions were made, the data collected were systematized and analyzed, in order to consolidate the last specific objective, which is to understand how polyaffective families are inserted in this process of [not] legal and sociocultural recognition in Brazil, from their experiences.Throughout this study, it was possible to verify that polyaffective families desire for protection, security and judicial guardianship, in addition to the recognition of their unions in the social environment, with a due preservation of their private autonomy and family planning.